Leveraging ancillary benefits from urban greenspace – a case study of St. Louis, Missouri. Issue 3 (16th March 2022) - Jordan, Page; Hoover, Fushcia-Ann; Hopton, Matthew E.
ABSTRACT: Urban greenspace and green infrastructure are often cited for their many ecosystem services and benefits including stormwater management. However, the localized nature and limited range of effects of these benefits and the type of greenspace and green infrastructure, make planning and placement critical components to selecting for and maximizing desired benefits. Here, the authors test a framework to demonstrate a practical approach to simultaneously manage excess stormwater and maximize distribution of ecosystem services to underserved areas using spatial analysis. St. Louis was subdivided using census block polygons and polygons identified have combined sewer systems with high aggregate annual discharge. Additionally, indicators representing social, economic, and environmental characteristics, which have demonstrated effects from greenspace, were mapped to identify spatial distribution and overlap. The analysis identified one polygon that could promote multiple desired ecosystem services, while reducing annual discharge into combined sewers, and provide these services to an underserved demographic.